PENGARUH PROGRAM DIRECT MARKETING TERHADAP KEPUTUSAN MENGGUNAKAN MEETING PACKAGE HOTEL GRAND PREANGER BANDUNG : Survei Pada Tamu Bisnis Yang Menggunakan Meeting PackageHotel Grand Preanger Bandung - Nogus Pahliawan, - (2010)
MICE (meetings, incentive, convention and exhibition) industry is one part of the tourism sector is currently experiencing rapid development. MICE events not only generate income for the parties directly related to MICE events, but also involves a lot of indirect economic actors. So is the MICE industry in Indonesia has a major contribution to foreign exchange for Indonesia. MICE sector in Indonesia accounted for 40% of the total foreign exchange earnings from tourism. MICE hotel as a supplier, one of them is Grand Preanger Hotel's. Many hotels in Bandung, which was then staged on the MICE industry, leading to high competition. Grand Preanger Hotel's efforts to increase sales meeting one of package by running promotional programs. Promotion holds a very important role in a business, with the promotion and sustainable implementation of the planned is expected to increase sales of meeting package. One of the promotional programs are carried Grand Preanger Hotel's direct marketing programs. The purpose of this research is to know how big influence of direct marketing programs that consist of direct selling, direct mail and telemarketing to decision using the meeting package. The object under study is a business guest at the Grand Preanger Hotel's. The method used in this research is descriptive and explanatory survey. The number of samples is 70 respondents, using technique stratified random sampling. The data used are primary and secondary data collected through observation, questionnaires, literature, and interviews. The results showed that the direct-marketing program consisting of direct selling, direct mail and telemarketing have a significant impact in deciding the business guests to use Grand Preanger Hotel meeting packages.